Will ChatGPT revolutionize accounting? The benefits of Artificial Intelligence (AI) in accounting; Analysis of the significance of employer branding in generations Y and Z - Bernd Hacker (Technische Hochschule Rosenheim, 2023)
It's an experiment! This paper explores how ChatGPT can be used in accounting and reporting to automate routine tasks, increase efficiency, and better understand financial data. The creation of the paper itself was done with the help of ChatGPT, i.e., significant parts of this text were created by the AI and then edited and completed by the author in terms of content and language. On the one hand, this is intended to show the potential of the application in practice and to make it clear that dealing with the tools of AI will be indispensable in the future, but on the other hand, the risks and concerns are also addressed.
urn:nbn:de:bvb:861-opus4-21340
Keywords: 650; ChatGPT; Artificial intelligence; Chatbot; Accounting; Appendix; Auditing